2018
DOI: 10.1111/ijfs.13767
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a neural network model for predicting growth of Salmonella Newport on diced Roma tomatoes during simulated salad preparation and serving: extrapolation to other serotypes

Abstract: Summary A study was undertaken to model growth of Salmonella on tomatoes for developing and validating a predictive model for use in risk assessment. Cylindrical portions (0.14 g) of Roma tomato pulp were inoculated with a low dose (0.89 log MPN) of Salmonella Newport. The inoculated tomato portions were incubated for 0–8 h at 16–40 °C in 2 °C increments to obtain most probable number (MPN) data for model development and validation. A multiple‐layer feedforward neural network model with two hidden layers of tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 32 publications
0
19
0
Order By: Relevance
“…Furthermore, these products are generally investigated considering mix of vegetables, but very limited information are available on the bacterial evolution of mono‐varietal salads to predict the microbial dynamics of each species. The development and validation of food models for predicting growth of given pathogenic bacteria is of relevance (Oscar, ) for future applications on ready‐to‐eat vegetable salads.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, these products are generally investigated considering mix of vegetables, but very limited information are available on the bacterial evolution of mono‐varietal salads to predict the microbial dynamics of each species. The development and validation of food models for predicting growth of given pathogenic bacteria is of relevance (Oscar, ) for future applications on ready‐to‐eat vegetable salads.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a model (multiple‐layer feed forward neural network) for growth of the same strain of Salmonella Newport (0.85 log) on Roma tomato portions (0.14 g) incubated at times (0–8 hr) and temperatures (16–40°C) observed during meal preparation was developed and validated (interpolation) using the APZ method (Oscar, ). This model was also validated for extrapolation to other serotypes of Salmonella (e.g., Montevideo, Thompson, Hadar, Heidelberg, and Typhimurium var 5‐) using the APZ method.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the current model can be improved by validating it for extrapolation to other serotypes and if serotypes are found that grow differently than Salmonella Newport, the model could be expanded to include these serotypes as was done in a previous study (Oscar, ). In general, most serotypes of Salmonella have similar growth kinetics (Oscar, , ) but a few, such as Enteritidis (Oscar, ), Kentucky (Oscar, ), and 8.20:–: z 6 (Oscar, ), grow slower…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, S. Typhimurium, as a major foodborne pathogen (Oscar, ), was employed to explore the relationships among growth temperature, fatty acid composition of cytomembrane and PEF resistance of S. Typhimurium cells. The alteration of fatty acid composition induced by different growth temperatures was analysed and thus the correlation between PEF resistance and membrane fatty acid composition of cell was elucidated.…”
Section: Introductionmentioning
confidence: 99%